2016
DOI: 10.4028/www.scientific.net/kem.679.63
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Multi-Nozzle near Field Electrospinning: Experimentation and Simulation

Abstract: There are massive reports about near-field electrospinning (NFES) in the literature and the NFES has great tendency for scientific and industrial applications. It is important to improve the machining efficiency of electrospinning. Through the study of the multi-nozzle near-field electrospinning, a new method by adjusting the electrode-to-collector distance (E-C-D) is presented in this paper to make sure the jets with a straight line. The method is divided into two steps: (1) to adjust the E-C-D larger to get … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The mentioned NFES approaches above are all assembled with single nozzle, however, due to the flow restriction, single-nozzle NFES system is unable to cope with mass production, which limits the industrial utilization in precision manufacturing. To improve the high-precision production efficiency and rate, a multinozzle NFES system (Figure ) was presented. On the basis of the mutual influence of the charged jets under shifty conditions, the deposition characteristics of double-nozzle and triple-nozzle NFES systems have been demonstrated and analyzed. The mutual distance of deposition was mainly influenced by nozzle spacing and working distance, on the other hand, the influence of voltage was not particularly apparent, and analysis suggested that the main reason for these phenomena may be the function of Coulomb force.…”
Section: Progress and Mechanism Of Nfesmentioning
confidence: 99%
“…The mentioned NFES approaches above are all assembled with single nozzle, however, due to the flow restriction, single-nozzle NFES system is unable to cope with mass production, which limits the industrial utilization in precision manufacturing. To improve the high-precision production efficiency and rate, a multinozzle NFES system (Figure ) was presented. On the basis of the mutual influence of the charged jets under shifty conditions, the deposition characteristics of double-nozzle and triple-nozzle NFES systems have been demonstrated and analyzed. The mutual distance of deposition was mainly influenced by nozzle spacing and working distance, on the other hand, the influence of voltage was not particularly apparent, and analysis suggested that the main reason for these phenomena may be the function of Coulomb force.…”
Section: Progress and Mechanism Of Nfesmentioning
confidence: 99%